The role of forensic sexology and a court expert witness in the fight against sexual crimes and for public health - Mazurkiewicz, Dariusz Wojciech; Załuski, Janusz; Strzelecka, Jolanta; Kondraciuk-Wróblewska, Walentyna; Siemienkowicz, Joanna (Polish Journal of Public Health, 2013)
The aim of forensic sexology as knowledge and science is to conduct research and to define standard principles of sexuality as well as to identify its deviations based on the results of a research studies of the said issue, applying and relating to the law in force. The role of an expert witness is indispensable There are instances of evidence manipulation by the party filing a sexual abuse lawsuit; however, the justice system is equipped with means to prevent it. The efficacy of the therapeutic and medical treatment of the offenders is disturbed many a time or even unfeasible due to the lacking consent on the part of the culprit and/or the lack of appropriate legal regulations. This affects the well-being of the society.